The Effect Of Perceived Organizational Support (POS) And Work-Life Balance (WLB) On The Performance Of Elementary School Teachers In Sukabumi Regency - Ijey; Rismawati; Endah (Eudaimonia Journal Psychology, 2026)
This study aims to analyze the effect of Perceived Organizational Support (POS) and Work Life Balance (WLB) on the performance of elementary school teachers in Sukabumi Regency. The background of this research is based on the low performance of teachers, most of whom hold honorary status, and the large number of school principal positions filled by acting officials (PLT), indicating that organizational support for educators has not been optimized. This study employed a quantitative approach using a survey method with 208 teachers selected through purposive sampling from a population of 9,352 teachers. Data were collected using questionnaires adapted from the Survey of Perceived Organizational Support (SPOS) instrument (Eisenberger et al., 1986), the Work Life Balance Scale (Fisher et al., 2009), and The Danielson Framework for Teaching (Danielson, 2022), and were analyzed using multiple linear regression with SPSS. The results indicate that POS has a positive and significant effect on teacher performance (sig. = 0.011), whereas WLB does not have a significant effect (sig. = 0.388). Simultaneously, both variables significantly affect teacher performance (sig. = 0.002), contributing 5.1% of the variance. It is concluded that organizational support is the dominant factor in improving teacher performance. Schools and education departments are recommended to strengthen organizational support through proportional recognition and the provision of adequate work facilities.